2019
DOI: 10.1103/physrevmaterials.3.043602
|View full text |Cite
|
Sign up to set email alerts
|

Primary damage production in the presence of extended defects and growth of vacancy-type dislocation loops in hcp zirconium

Abstract: Production rates in long-term predictive radiation damage accumulation models are generally considered independent of the material's microstructure for reactor components. In this study, the effect of pre-existing microstructural elements on primary damage production in α-Zr -and vice-versa-is assessed by molecular dynamics (MD) simulations. -type dislocation loops, -component dislocation loops and a tilt grain boundary (GB) were considered. Primary damage production is reduced in the presence of all these mic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…The number density of dislocation <a> loops is about to 2.6 × 10 15 m −2 at 350 °C and 3.4 × 10 15 m −2 at 400 °C, respectively. The density of vacancy <a> loops at both temperatures is less than 1 × 10 15 m −2 , which are insufficient to produce <c> dislocation loops by mechanism of coalescence and collapse 31 . Notably, profuse tiny <c> dislocation loops were also detected in the sample irradiated at 400 °C, as shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The number density of dislocation <a> loops is about to 2.6 × 10 15 m −2 at 350 °C and 3.4 × 10 15 m −2 at 400 °C, respectively. The density of vacancy <a> loops at both temperatures is less than 1 × 10 15 m −2 , which are insufficient to produce <c> dislocation loops by mechanism of coalescence and collapse 31 . Notably, profuse tiny <c> dislocation loops were also detected in the sample irradiated at 400 °C, as shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…From atomic-scale modeling, a mechanism for <c> loop generation based on the collapse of irradiation-produced pyramids has been proposed 30 . Unlike the prior proposals, the formation of <c> loops in this case would be independent of the formation of <a> vacancy loops, and would instead require the collapse of a stacking fault pyramid that has grown beyond a critical size [30][31][32] . However, to date, these irradiation-induced pyramidal defects in Zr have not been observed.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The number of residual point defects was evaluated and compared with that in the pristine material under the same irradiation conditions. Dai et al [14] used molecular dynamics simulations to reveal that the primary damage production was reduced due to the presence of a-type dislocation loops, c-component dislocation loops and a tilt grain boundary. Fu et al [15] found that the residual vacancy number usually exceeded the residual interstitial number when the displacement cascades interacted with straight edge dislocation in tungsten via a molecular dynamics simulation.…”
Section: Introductionmentioning
confidence: 99%
“…This was later demonstrated using computer simulations of cascade overlap, where the number of new defects was reduced as a consequence of overlap [8] . Since then, simulations of cascade overlap have been carried out in a number of materials, including Ni and Ni-based alloys [9] , Fe and Fe-based alloys [10][11][12] , equiatomic multicomponent alloys [13,14] , Zr [15][16][17] and recently also in In x Ga 1 −x N [18] .…”
Section: Introductionmentioning
confidence: 99%